Managing the Internationalization Processes of Universities - Aleksandra KUZIOR; Dariusz KRAWCZYK (Communications of International Proceedings, 2021)
The paper concerns the management of internationalization processes of universities, emphasizing the role of a strategic partner, which is the local government unit, in the area of which the university operates. The authors present a case study referring to the City of Zabrze (a city with poviat rights – Poland, Upper Silesia), where two out of fifteen faculties of the Silesian University of Technology, the largest university in the region, and one faculty of the Medical University of Silesia are located. The authors point to the great role of institutional, organizational and financial support from the City of Zabrze for the universities. From the perspective of the raised subject, contacts with partner cities as well as information-and-promotion activities carried out among foreign investors are particularly important. Internationalization activities are considered from the perspective of strategic management. The paper uses case studies presenting the cooperation of universities located in Zabrze (Poland) with local government authorities. Zabrze is a strategic partner of the university in the processes of internationalization.
Keywords: Internationalization; Universities; Strategic Management; Academic Mobility; Local Government Unit